Education of The 5 Pillars Management Based on Caring For Blood Sugar Levels in Diabetes Mellitus Type II - Hosnu Inayati; Zakiyah Yasin; Dian Ika Puspitasari; Ahmad Nawawi (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Diabetes Mellitus is currently still a chronic disease due to high blood sugar levels, cannot be cured and can only be controlled so that sugar levels remain stable and normal. Uncontrolled blood sugar can increase the risk of complications such as gangrene, stroke, coma and death. Batang-Batang Daya Village, Batang-Batang District, Sumenep Regency has 2,371 patients with Type-II Diabetes Mellitus. The number of diabetics is increasing because people do not understand the management of Diabetes Mellitus. Therefore it is necessary to involve all parties such as the village community, local government, community leaders, health workers, and families to assist in controlling blood sugar levels in people with Diabetes Mellitus. The form of community service activities that we carry out are conducting counseling about Diabetes Mellitus and the 5 pillars of management for type-II Diabetes Mellitus sufferers, checking blood glucose levels and blood pressure. The purpose of this community service is that people are able to know from an early age the 5 types of Diabetes Mellitus, the community is able to know from an early age the 5 pillars of management for people with Diabetes Mellitus. The method of carrying out activities is the counseling method and comprehensive blood sugar checks regarding the 5 pillars of Diabetes Mellitus management, namely education, food planning, physical exercise, pharmacological intervention or the use of blood glucose-lowering drugs, and blood sugar.